Flea (Insecta: Siphonaptera) Family Diversity - Bossard, Robert L. (2023)
This overview of extant Siphonaptera lists 19 families with major hosts and their general distribution, estimated numbers of genera, species, and subspecies, with a brief taxonomic and phylogenetic review. With around 10 new species described annually, extant flea fauna comprises an estimated 249 genera, 2215 species, and 714 subspecies globally, mostly mammal parasites, but 5% of species are on birds. Host specificity varies from euryxenous (i.e., infesting two or more host orders) (e.g., cat fleas, Ctenocephalides felis felis) to monoxenous (e.g., rabbit fleas, Spilopsyllus cuniculi). The largest family is the paraphyletic Hystrichopsyllidae, making up a third of all flea species. The largest monophyletic family, Ceratophyllidae (rodent and bird fleas), comprises another 20% and has dispersed to every continent, including Antarctica. Fleas descend from scorpionflies (Mecoptera), possibly snow scorpionflies (Boreidae) or Nannochoristidae, and even giant fossils found from the Mesozoic could be Siphonaptera. The diversification of fleas shows evidence of taxon cycles. “Relict” families, such as helmet fleas (Stephanocircidae), have a disjunct distribution reflecting the breakup of Gondwanaland 70 million years ago. “Niche specialists” include nest fleas (Anomiopsyllus), bat fleas (Ischnopsyllidae), and burrowing fleas, such as chigoes (Tungidae). By contrast, Ceratophyllidae fleas could be considered “great speciators”. Cat fleas and several other synanthropic flea species are invasive “supertramps”. Although those species are intensively studied, many flea species and their hosts require urgent surveys and conservation.